CHARACTER BASED HOLISTIC CURRICULUM MANAGEMENT IN TABANAN ISLAMIC PRIMARY SCHOOL - Cindy Anggraini Widodo (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
The researcher aims to describe and analyze character-based holistic education management at the Tabanan Islamic Elementary School. The research focuses on planning, organizing, implementing and evaluating in improving the quality of curriculum education with a holistic, character-based approach in the school. This research uses descriptive-qualitative research methods using observation, interviews and documentation as data collection techniques. The analysis techniques used in this research are data collection, data reduction, data presentation, drawing conclusions. The triangulation used to test the validity of the data is technique and source triangulation. The results of this research show that this character-based holistic approach has been successful in cultivating character in Tabanan Islamic Elementary School students. In the teaching process, this approach develops two types of learning, namely a holistic character development program, and character education that is integrated with contextual subjects.